Analysis of the Welfare Level of Rice Farmers Using the Farmer's Exchange Rate (FER) Approach and Factors Affecting FER in South Tapanuli Regency - Fithra Maharani; Lilis Saryani; Iswandi Idris (SEAN Institute, 2022)
Data released by BPS North Sumatra shows that rural poverty in September 2020 is at 600.48 thousand people or 9.02 percent. The low economic value in the agricultural sector results in a low level of farmer welfare. Farmer's exchange rate (FER) is one indicator of farmers' welfare. FER can be measured by comparing the price index received by farmers (output selling price index) with the price index paid by farmers (production process input price index). Agricultural development can contribute to national development and is the largest contributor to both national GDP and regional GDP. There are several factors that affect the exchange rate of farmers themselves, including: Consumer Price Index (CPI), GDP, and rice prices. The purpose of the study was to determine the farmer's exchange rate (FER) and the factors that influence the farmer's exchange rate in South Tapanuli Regency. Methods: Research Location: Tatengger Village, Angkola Muara Tais District, South Tapanuli Regency. Type of data: primary data, primary data. Population: all rice farmers in Tatengger Village, Angkola Muara Tais Sub district, Tapsel Regency, as many as 127 farmers; the sampling used the Krejcie and Morgan method; as many as 56. Data analysis methods: calculating FER, Calculating FER factors. From the analysis that has been carried out regarding the Analysis of Rice Paddy Farmers' Exchange Rates in Tatengger Village, Angkola Muara Tais District, South Tapanuli Regency, the conclusions are: On average, the Farmer's Exchange Rate (FER) of the sample in Tatengger Village is 96.87 or less than 100 Thus, it can be concluded that the welfare level of the sample farmers in Tatengger Village, Angkola Muara Tais District, South Tapanuli Regency in 2020 is classified as not yet prosperous.